2021
DOI: 10.1080/00779954.2020.1870534
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 experience in the Fiji Islands: some lessons for crisis management for small island developing states of the Pacific region and beyond

Abstract: The COVID19 global pandemic has seriously disturbed Fiji, its people and the economy. Consequently, crisis management has been highly challenging in this small and vulnerable economy. Although the number of positive cases was low, the economic impact of COVID19 has been significant. In this paper, we identify several crisis management issues to better deal with the pandemic. These discussions can potentially improve Fiji's response strategies and initiatives to safeguard public health and economic activity. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Finally, the power of the political determinants of health in shaping authorities’ pandemic planning and response throughout the Pacific region is highlighted by this research. 43 , 44 , 45 Study findings demonstrate clear need for ongoing longitudinal research investigating the political determinants of health in emergency and disaster contexts through the leadership and governance WHO building block lens. In this study, politics, governance and trust have been confirmed as crucial ‘software’ elements for LMIC health system disease outbreak preparedness.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, the power of the political determinants of health in shaping authorities’ pandemic planning and response throughout the Pacific region is highlighted by this research. 43 , 44 , 45 Study findings demonstrate clear need for ongoing longitudinal research investigating the political determinants of health in emergency and disaster contexts through the leadership and governance WHO building block lens. In this study, politics, governance and trust have been confirmed as crucial ‘software’ elements for LMIC health system disease outbreak preparedness.…”
Section: Discussionmentioning
confidence: 91%
“…The COVID-19 pandemic could be responsible for this decrease as Fiji relies on imported antimicrobials. This also shows how vulnerable Pacific Island Countries are to external shocks such as pandemics which may affect food security (Singh et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Fiji Island is already battling with challenges related to climate change and natural disasters including cyclones. The COVID-19 pandemic has compounded this, by revealing the vulnerability and the limited capacity of the healthcare system (Leal Filho et al ., 2020; Singh et al. , 2022) and limited Internet accessibility (Mukuna and Aloka, 2020; Tadesse and Muluye, 2020).…”
Section: Introductionmentioning
confidence: 99%